Thermal Hysteresis and Bursting Rate in Sucrose Solutions with Antifreeze Proteins - KIRAN YILDIRIM, BERÇEM (WILEY-V C H VERLAG GMBH, 2020)
Antifreeze proteins (AFPs) modify the ice shape and inhibit further growth leading to thermal hysteresis (TH). Numerous studies have been performed with the addtition of AFPs to preserve frozen products but the influence of sucrose on the effects of AFPs has not been investigated as of yet. Therefore, the TH activities of type I antifreeze protein (AFP I) and antifreeze glycoprotein (AFGP) were measured as a function of concentration, type of AFPs, and also sucrose concentration. The results showed that the TH values rose with increase in concentration of AFPs and sucrose concentration. The crystals experienced shape modification and grew in the c-axis direction in the presence of both AFPs. The bursting rate of crystals changed depending on both the concentrations of AFPs and sucrose.
Keywords: Antifreeze proteins; Ice-binding proteins; Ice crystals; Sucrose solution; Thermal hysteresis; WINTER FLOUNDER ANTIFREEZE; ICE STRUCTURING PROTEINS; RECRYSTALLIZATION INHIBITION; ENHANCEMENT; GLYCOPROTEINS; POLYPEPTIDE; MECHANISMS; CRYSTALS; BINDING